Manajemen Lembaga Pendidikan dalam Pelaksanaan Pembelajaran Tatap Muka Terbatas - Ramdanil Mubarok (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The Covid-19 pandemic has shown a downward trend, allowing for limited face-to-face learning. The purpose of writing the article is to analyze the concept of limited face-to-face learning and the management of its implementation. The method used is a qualitative research method with the type of library research (library research). The result is that the concept of implementing face-to-face learning (PTM) is limited to the Covid-19 pandemic, which is a learning model carried out in educational institutions face-to-face which is limited to the number of students, a number of meetings, meeting hours and subject matter with terms and conditions that have been set. The management of the implementation of face-to-face learning is limited, namely by careful planning, proper organization, effective and efficient implementation, as well as intense supervision by monitoring, having evaluation instruments, and reporting. It is hoped that through this article the implementation of limited face-to-face learning can be carried out in accordance with expectations, and is able to provide suggestions for improvement.